2023
DOI: 10.1088/1741-2552/ace7f7
|View full text |Cite
|
Sign up to set email alerts
|

High-density magnetomyography is superior to high-density surface electromyography for motor unit decomposition: a simulation study

Abstract: Objective: 
Studying motor units (MUs) is essential for understanding motor control, the detection of neuromuscular disorders and the control of human-machine interfaces. Individual motor unit firings are currently identified in vivo by decomposing electromyographic (EMG) signals. Due to our body’s properties and anatomy, individual motor units can only be separated to a limited extent with surface EMG. Unlike electrical signals, magnetic fields do not interact with human tissues. This physical propert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 54 publications
(18 reference statements)
0
3
0
Order By: Relevance
“…We have demonstrated the similarities of MMG to sEMG and highlighted some differences which may allow for better localization using MMG compared to sEMG. Though advantages in localization have been shown in models (Arekhloo et al, 2022; Klotz et al, 2022, 2023), there has yet to be empirical evidence. Magnetic sensing of the brain (magnetoencephalography (MEG)) has been demonstrated to provide higher localization accuracy compared to electrical sensing (electroencephalography (EEG)) in both a phantom as well as an implanted dipole in humans (Cohen et al, 1990; Cohen & Cuffin, 1991; Leahy et al, 1998), but the results cannot be extended to muscle sensing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have demonstrated the similarities of MMG to sEMG and highlighted some differences which may allow for better localization using MMG compared to sEMG. Though advantages in localization have been shown in models (Arekhloo et al, 2022; Klotz et al, 2022, 2023), there has yet to be empirical evidence. Magnetic sensing of the brain (magnetoencephalography (MEG)) has been demonstrated to provide higher localization accuracy compared to electrical sensing (electroencephalography (EEG)) in both a phantom as well as an implanted dipole in humans (Cohen et al, 1990; Cohen & Cuffin, 1991; Leahy et al, 1998), but the results cannot be extended to muscle sensing.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated robust recordings of MMG and have applied analyses including stimulus triggered averages of muscle activity (Broser et al, 2018), decoding of individual motor units (Broser et al, 2023), and even discrimination between movements that rival results obtained with sEMG (Greco et al, 2023). Models and simulations have also shown MMG has higher specificity and better localization compared to sEMG, furthering excitement for the field (Arekhloo et al, 2022; Klotz et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…The majority of evidence on the inhibitory control of PICs arises from animal studies and computer models (Hultborn et al ., 2003; Kuo et al ., 2003; Hyngstrom et al ., 2007; Bui et al ., 2008) but the magnitude of PICs in human motoneurons can be estimated quite easily due to recent advances in technology and analysis techniques (Klotz et al ., 2023; Möck & Del Vecchio, 2023). There remains a scarcity of research in humans, however, that establishes a relationship between reciprocal inhibition and PIC magnitude (Thorstensen, 2022).…”
Section: Introductionmentioning
confidence: 99%